2014
DOI: 10.1097/wnr.0000000000000121
|View full text |Cite
|
Sign up to set email alerts
|

Reading skill and structural brain development

Abstract: Reading is a learned skill that is likely influenced by both brain maturation and experience. Functional imaging studies have identified brain regions important for skilled reading, but the structural brain changes that co-occur with reading acquisition remain largely unknown. We investigated maturational volume changes in brain reading regions and their association with performance on reading measures. Sixteen typically developing children (5-15 years old, 8 male, mean age of sample=10.06 ±3.29) received two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 21 publications
2
37
0
1
Order By: Relevance
“…This pattern is consistent with normal age-related reductions in gray matter that take place throughout adolescence and early adulthood [58]. This reduction in gray matter volume has been linked to better cognitive functioning across a variety of domains [59]. In the current study, we observed larger volume of the corpus medullare and inferior posterior cerebellar lobe among individuals with a family history of alcohol dependence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This pattern is consistent with normal age-related reductions in gray matter that take place throughout adolescence and early adulthood [58]. This reduction in gray matter volume has been linked to better cognitive functioning across a variety of domains [59]. In the current study, we observed larger volume of the corpus medullare and inferior posterior cerebellar lobe among individuals with a family history of alcohol dependence.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, adolescent cannabis users show significantly larger inferior posterior (lobules VIII–X) vermis volume than controls while alcohol use was associated with smaller posterior inferior volume [61]. Although family history of substance use disorders was not assessed in the Houston et al study [59], it is possible that the larger volume seen among these cannabis users may reflect family history differences in susceptibility for substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Further, spelling was associated with two bilateral cortical regions in the temporal cortices. Reading, while impaired in alcohol-exposed children relative to controls, did not appear to have cortical surface area correlates and may relate to broader neural circuitry dysfunction or differential trajectories (Houston et al, 2014, Ashkenazi et al, 2013). Further, there were no differential associations with cortical thickness, suggesting it may not be as sensitive an indicator for prenatal alcohol exposure (Gross et al, 2016) or the use of an alcohol-exposure group may not be as sensitive in detecting cortical effects of thickness as other continuous measures of alcohol exposure (Meintjes et al, 2014, Roberston et al, 2016).…”
Section: Discussionmentioning
confidence: 74%
“…Growing literature supports both cognitive mechanisms and specific neural correlates that underlie distinct academic pathways. Neuroimaging findings suggest that structural or functional changes in the brain may contribute to academic performance in typically developing children (Houston et al, 2014, Dehaene et al, 2003), and those with learning disorders (Ashkenazi et al, 2013). Relatively few studies have examined these relations in alcohol-exposed populations, however relations of math performance to brain structure and function have been reported (Woods et al, 2015, Lebel et al, 2010, Meintjes et al, 2010, Santhanam et al, 2009), whereas associations with reading or spelling were not assessed in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The prenatal period is the most sensitive time window to the influence of environmental factors on cognitive development, when brain development involves neuronal proliferation, differentiation, and migration (Kang et al 2011; Stiles and Jernigan 2010). Reading ability is central to educational attainment and academic achievement, and is predominantly influenced by the development in the brain reading region (Houston et al 2014). Studies have reported that a child’s reading ability was impaired by prenatal maternal smoking exposure (Cho et al 2013).…”
Section: Introductionmentioning
confidence: 99%